TINJAUAN YURIDIS TINDAK PIDANA PEMBUNUHAN YANG DILAKUKAN OLEH ANAK - MASYHUR MASYHUR (GANEC SWARA, 2018)
The purpose of this research is to know the application of material criminal law on murder crime committed by child and to know judge's legal consideration in imposing criminal punishment on child as perpetrator of murder crime. This research uses qualitative descriptive method with data source used in the form of primary data by conducting interviews to related parties and secondary data in the form of documents relevant to the research. Based on the results of research and discussion it can be known factors causing the crime of murder on children committed by child perpetrators in which consists of two factors, namely internal factors (derived from within the human), the personality factor (in the child), and biological factors, while external factors (derived from outside the human self), namely family factors, environmental factors, lack of provision of religion, and technological developments. It can also be seen that efforts to tackle criminal acts of murder committed by child perpetrators against children are preventive measures by non-punishment by providing religious supplies to children, as well as the active role of the community and school educators in supervising, preventing children from behaving towards irregularities and teaching and informing good things to children by the family and efforts to overcome the perpetrators of the crime of murder committed in this case through the penalty line may be imposed under Articles 338, 339 of the Criminal Code and Law no. 3 Year 1997 on Juvenile Court. The advice given by the author, among others, to parents should equip their children with the science of religion, provide positive activities, provide motivation for children, and provide a good example. To the public should pay attention to the condition of the surrounding environment so that children do not do things that are not desirable